Design and optimization of a space net capture system based on a multi-objective evolutionary algorithm. (February 2020) - Chen, Qingquan; Zhang, Qingbin; Gao, Qingyu; Feng, Zhiwei; Tang, Qiangang; Zhang, Guobin
Abstract: Space net capture is an innovative concept for active debris removal that provides a prospective method for the removal of large, non-cooperative space targets. The design of a space net capture system must meet two basic requirements: maximizing the capture ability and minimizing the system cost. This paper presents an inexpensive multi-objective optimization framework to solve this design problem. In this framework, a design optimization approach using a lumped parameter modelling method as well as an improved inexpensive multi-objective optimization algorithm is proposed. The system mass and effective distance are chosen as objectives of this optimization problem. The simulation results reveal that the multi-objective optimization framework is feasible and effective for the design of a space net capture system, and the designer preferred solutions that enhance system design are reliably identified. Highlights: A multi-objective optimal design framework for space net system is proposed. A lumped parameter model is studied and verified with ground test. System mass and effective working distance are chosen as optimization targets. MOEA/D EGO optimization algorithm is improved and used to solve this time expensive optimization problem. A new evaluation index, effective working distance, is proposed based on the target coverage ratio.